2008
DOI: 10.1002/hup.923
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention and serotonin: a pharmaco‐fMRI study

Abstract: The results of the current pharmaco-functional magnetic resonance imaging (fMRI) study give a first indication of involvement of serotonin in sustained attention through modulating activation of selective brain areas including the thalamus and caudate nucleus. Possibly, these areas are involved in a subcortical network for sustained attention, but further research is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 47 publications
(54 reference statements)
3
45
0
Order By: Relevance
“…Frontal cortex activity has been shown to increase after citalopram during the recognition of disgusted faces (Anderson et al 2007), whereas in a sustained attention task citalopram decreased prefrontal activity (Wingen et al 2008). Thalamic activity was reduced in the same study (Wingen et al 2008). However, during the recognition of disgusted faces, citalopram increased thalamus activity (Anderson et al 2007).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Frontal cortex activity has been shown to increase after citalopram during the recognition of disgusted faces (Anderson et al 2007), whereas in a sustained attention task citalopram decreased prefrontal activity (Wingen et al 2008). Thalamic activity was reduced in the same study (Wingen et al 2008). However, during the recognition of disgusted faces, citalopram increased thalamus activity (Anderson et al 2007).…”
Section: Discussionmentioning
confidence: 89%
“…For example, citalopram has been shown to increase amygdala activity in response to facial expressions (Bigos et al 2008) and without any stimulus (McKie et al 2005), but it has also been shown to reduce amygdala responses to fearful facial expressions (Murphy et al 2009). Frontal cortex activity has been shown to increase after citalopram during the recognition of disgusted faces (Anderson et al 2007), whereas in a sustained attention task citalopram decreased prefrontal activity (Wingen et al 2008). Thalamic activity was reduced in the same study (Wingen et al 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Concerning the post-scanning rating of the emotional pictures, we found no significant influence of the medication. Earlier studies found influences of the acute administration of citalopram (eg, Harmer et al, 2003;Bhagwagar et al, 2004) and reboxetine (De Martino et al, 2008;Miskowiak et al, 2007) on some emotional paradigms; others, however, found no significant behavioral effects of acute doses of citalopram Wingen et al, 2008) and reboxetine (O'Carroll and Papps, 2003) in emotional tasks.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth study concentrated on the changes in amygdalar activity during infusion of citalopram with an emotional face processing task (Bigos et al, 2008). Applying escitalopram, the s-enantiomer of citalopram, during a sustained attention task, Wingen et al, 2008 found increased activity only in right temporal regions, but decreased brain activity in thalamic, frontal, and premotor areas. A recent study (Murphy et al, 2009) applied 20 mg citalopram 3 h before fMRI using the masked and unmasked emotional faces, revealing a reduced activity of the right amygdala after unmasked fearful faces.…”
Section: Discussionmentioning
confidence: 99%